Gestão estratégica de suprimentos nas indústrias metalúrgica e mineral - Jose Carlos Martins Ferreira de Mello (2007)
The strategical suppliers management (GES) is an administrative tool that analyzes and later optimizes the relationship of an organization with it suppliers base. Based on data generated internally as total volume bought from each supplier (in a period of 12 months, for example) GES divides the suppliers in categories and establishes which is the best alternative of relationship of the organization with them. This work was carried through during 2006 in two companies of the metals andmining sector: Mineração J.Mendes (Itatiaiuçu MG) and Reframax Ltda a company specialized in refractory constructions. The results, still initial, indicate reductions of acquisition costs, improvements in thepurchasing department administration and better understanding of the purchasing processes by the strategical levels of the organizations.